Penatalaksanaan Fisioterapi pada Carpal Tunnel Syndrome Dextra dengan Ultrasound, Infared dan Terapi Latihan - Pretty Titan Al humaira; Kuswardani Kuswardani (Lembaga Pengembangan Kinerja Dosen, 2026)
Carpal tunnel syndrome (CTS) is a disease of the wrist caused by repetitive movements in an abnormal position continuously and for a long time, so that the median nerve in the wrist becomes pinched or compressed. Risk factors that may influence the event CTS include age, gender, and occupational factors. The problem experienced by the patient is pain in the wrist, tingling in the palms that spreads to the fingers. Therefore the provision of interventions using ultrasound aims to reduce pain, laser aims to reduce pain and inflammation, andexercise therapy aims to increase the range of motion of the joints, increase muscle strength, and restore functional activity.This scientific paper is a case study in nature, raising patient cases and collecting data through a physiotherapy process. The modalities provided are Ultrasound, Infrared, and Nerve Tendon Gliding Exercise. After 4 times physiotherapy, the results showed a decrease in pain, a decrease in paraesthesia/tingling, an increase in the range of motion of the joints, an increase in muscle strength, and an increase in the ability of functional activities with the WHDI index. Physiotherapy management with Ultrasound, Infrared and Exercise Therapy modalities carried out in Carpal Tunnel Syndrome Sinistra cases for 4 times of therapy can reduce pain, paraesthesia/tingling, increase joint range of motion, increase muscle strength, and increase functional activity with the WHDI index.